2012
DOI: 10.1007/s12026-012-8287-5
|View full text |Cite
|
Sign up to set email alerts
|

Trichinella spiralis: shaping the immune response

Abstract: The co-evolution of a wide range of helminth parasites and vertebrates represented a constant pressure on the host's immune system and a selective force for shaping the immune response. Modulation of the immune system by parasites is accomplished partly by dendritic cells. When exposed to helminth parasites or their products, dendritic cells do not become classically mature and are potent inducers of Th2 and regulatory responses. Treating animals with helminths (eggs, larvae, extracts) causes dampening or in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 80 publications
4
76
0
Order By: Relevance
“…The TsTPX2 and TsTPX3 genes were up-regulated in the Ad3 stage of T. spiralis, as detected by qRT-PCR. During primary infection with T. spiralis (first 1-2 days), the parasite mainly elicits Th1-type host response (Ilic et al, 2012). However, Trichinella then stimulates dendritic cells (DCs) to shift the immune response to a predom- Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TsTPX2 and TsTPX3 genes were up-regulated in the Ad3 stage of T. spiralis, as detected by qRT-PCR. During primary infection with T. spiralis (first 1-2 days), the parasite mainly elicits Th1-type host response (Ilic et al, 2012). However, Trichinella then stimulates dendritic cells (DCs) to shift the immune response to a predom- Fig.…”
Section: Discussionmentioning
confidence: 99%
“…inantly Th2 response at 3 days after infection (Ilic et al, 2012). Several TsTPXs were shown to drive a Th2 response through alternatively activated macrophages (Donnelly et al, 2005;Donnelly et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…A second immunization was performed in the same manner as the primary immunization 10 days later. In the NP-KLH immunization, 10 g of NP 14 -KLH (Biosearch Technologies Inc., Novato, CA) was absorbed in alum and inoculated into mice intraperitoneally. In some experiments, naive OT-II TCR T cells (Thy1.1 Ϫ Thy1.2 ϩ ) were purified from spleen cells of OT-II TCR Tg mice using a naive CD4 ϩ T cell purification kit (Miltenyi Biotec, Bergisch Gladbach, Germany) and 1 ϫ 10 6 purified OT-II T cells were adaptively transferred into Thy1.1 mice previously infected with T. pseudospiralis 10 days before.…”
Section: Methodsmentioning
confidence: 99%
“…IL-6 signaling, IL-21 signaling, and inducible costimulator (ICOS) signaling are critical mediators for Tfh cell differentiation. Several studies have indicated that Trichinella infection affects Th1 as well as Th2 responses (14,15), whereas the influence of trichinellosis on Tfh responses has not yet been assessed.…”
mentioning
confidence: 99%
“…The muscle phase of the infection is further characterized by the existence of Treg cells. It is likely that chronic stimulation through ES L1 released into the circulation during the muscle phase of T. spiralis infection can activate regulatory network elements as guardians of homeostasis [9]. Immune events orchestrated by Th2 and Treg cell types can successfully modulate the immune response of the host [10].…”
Section: Introductionmentioning
confidence: 99%